2018
DOI: 10.1186/s12879-018-3326-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic burden of pneumococcal disease in US adults aged 19–64 years with chronic or immunocompromising diseases: an observational database study

Abstract: BackgroundDespite the widespread availability of pneumococcal vaccines, rates of pneumococcal disease are disproportionately high in adults with chronic and immunocompromising conditions. This study investigated pneumococcal disease rates and associated resource utilization and costs in this group.MethodsA retrospective, observational study was conducted using the Truven Health MarketScan® Commercial Claims and Encounters database. The study population was adults aged 19–64 years with continuous health plan en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 15 publications
0
59
0
6
Order By: Relevance
“…Because the more broadly vaccinations are implemented, the stronger both individual immunity and herd immunity becomes, the greater the benefits for everyone. Indeed, every study that has been done of the economic impact of pneumococcal and Hib vaccination programs has shown that for every billion dollars invested in vaccination, several billions are saved in critical care costs for elderly and atrisk patients (Wateska, et al, 2020;Richter, et al, 2019;Zhang, et al, 2018;Ciruela, et al, 2018;Baldo, et al, 2016;Arencibia Jiménez, et al, 2014;Isaacman, et al, 2008 ). Actual savings may be significantly greater since these economic studies have not included the benefits that may accrue from protection against the global economic devastation that a coronavirus or influenza pandemic can cause by shutting down businesses and harming trade.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the more broadly vaccinations are implemented, the stronger both individual immunity and herd immunity becomes, the greater the benefits for everyone. Indeed, every study that has been done of the economic impact of pneumococcal and Hib vaccination programs has shown that for every billion dollars invested in vaccination, several billions are saved in critical care costs for elderly and atrisk patients (Wateska, et al, 2020;Richter, et al, 2019;Zhang, et al, 2018;Ciruela, et al, 2018;Baldo, et al, 2016;Arencibia Jiménez, et al, 2014;Isaacman, et al, 2008 ). Actual savings may be significantly greater since these economic studies have not included the benefits that may accrue from protection against the global economic devastation that a coronavirus or influenza pandemic can cause by shutting down businesses and harming trade.…”
Section: Resultsmentioning
confidence: 99%
“…* Gervaix, et al, 2014;^ Mereckiene, 2017;+ WHO, 2020;> Blank, et al, 2018; # estimated from accumulated yearly vaccinations. Austria (Richter, et al, 2019); France (Contou, et al, 2020); Germany (Theidel, et al, 2013;Pletz, et al, 2016); Greece (Maraki, et al, 2018);US (FluVaxView;Wateska, et al, 2020;Zhang, et al, 2018;Sings, 2017;Williams, et al, 2016); UK (Tolman, et al, 2016); Australia (Hull, et al, 2019;Yang, et al, 2019;Dyda, et al, 2016); Japan (Naito, et al, 2020;Takeda, et al, 2019;Shibata, et al, 2019;Kajikawa, et al, 2019;Kumar, et al, 2014); S. Korea (Song, et al, 2013;Yang, et al, 2015;Park, et al, 2019;Yang, et al, 2020); Italy (Giammanco, et al, 2018;Baldo, et al, 2016;Tozzi, et al, 2014;Fedson, 2011); Spain (Ciruela, et al, 2018;Arencibia Jiménez, et al, 2014;Fedson, 2011); Canada (Kaplan, et al, 2019;Farmanara, et al, 2018); Portugal (Kislaya, et al, 2019); Netherlands (Vestjens, et al, 2019); Switzerland ** NB no current data available (Büla, et al, 1996). (TABLE 1).…”
mentioning
confidence: 99%
“…Chronic diseases and immunocompromise (IC), common in elderly population, are considered as two important risk factors in pneumococcal disease (PD) (Gil-Prieto et al, 2016). It has been presented as a significant cause which leads to substantial economic burden in at-risk and high-risk adults (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the number of immunocompromised patients is increasing due to ageing of the population, increased prevalence of chronic diseases as well as treatment with immunosuppressive agents [4,5]. Although immunocompromised patients have similar etiologies of acute RTI when compared to immunocompetent patients [6], they more often have a complicated course of the disease leading to high healthcare burden, especially in secondary and tertiary care settings [7,8]. Within the respiratory viral season, in-hospital isolation facilities are often falling short due to the high number of patients with suspected https://doi.org/10.1016/j.jcv.2019.04.003 Received 2 January 2019; Received in revised form 4 April 2019; Accepted 6 April 2019 viral infections and immunocompromised patients with prolonged viral shedding [9,10].…”
Section: Introductionmentioning
confidence: 99%